Rekonstruksi Penghentian Penuntutan Berbasis Kepentingan Hukum dalam Kerangka Diskresi dan Manajemen Risiko Sistem Peradilan Pidana - Sipayung, Baren; Zulkifli (CV. Kurnia Grup, 2025)
The enactment of Law Number 1 of 2023 on the Indonesian Criminal Code (the National Criminal Code) marks a fundamental shift from a colonial criminal law framework toward a national legal system grounded in substantive justice and the protection of human rights. Nevertheless, at the practical level, the implementation of these progressive norms is frequently constrained by a gap between law in books and law in action. This study examines the termination of prosecution in the Hogi Minaya case by the Sleman District Prosecutor’s Office as a critical intersection of prosecutorial discretion, socio-political pressure, and institutional risk management. Employing an interdisciplinary approach that integrates responsive criminal law theory and public risk management, the study reveals a significant implementation gap at the operational level of law enforcement agencies. The findings indicate that law enforcement authorities tend to adopt a defensive law enforcement approach to mitigate procedural accountability risks, which in turn leads to the marginalization of justificatory grounds under Article 34 of the National Criminal Code until legislative intervention occurs. This research proposes a new framework for understanding prosecutorial discretion not merely as a technical legal instrument, but as a form of strategic risk response aimed at preserving the legitimacy of the criminal justice system.